Partisan fiscal policy in a monetary union : asymmetric shocks, delegation and welfare - Pina, Álvaro M. (2021)
This paper studies the impact of partisan national fiscal policy on the optimal central bank design of a two-country monetary union. In each country two parties with different preferences compete for office, their succession in power being formalized as zero-mean political shocks. These contrast with supply disturbances both because political shocks call for more, rather than less, central bank conservatism and insofar as cross-country shock asymmetry is actually beneficial to welfare. Further, by combining Rogoff-type 'weight-conservatism' with an inflation target it is possible to ensure that monetary delegation always benefits both parties